Effect of implementation of a preconception counselling resource for women with diabetes: A population based study. Issue 1 (February 2017) - Holmes, V.A.; Hamill, L.L.; Alderdice, F.A.; Spence, M.; Harper, R.; Patterson, C.C.; Loughridge, S.; McKenna, S.; Gough, A.; McCance, D.R.; ,
Highlights: Pregnancy planning and pre-pregnancy care uptake is poor among women with diabetes. Poor preconception counselling is linked to poor pre-pregnancy care uptake. Implementation of a preconception counselling resource improved pregnancy planning. Women who engaged with the resource were better prepared for pregnancy. Women with type 2 diabetes, typically cared for in primary care, are hard to reach. Abstract: Aim: To evaluate the effect of regional implementation of a preconception counselling resource into routine diabetes care on pregnancy planning indicators. Methods: A preconception counselling DVD was distributed to women by diabetes care teams and general practices. Subsequently, in a prospective population-based study, pregnancy planning indicators were evaluated. The post-DVD cohort ( n  = 135), including a viewed-DVD subgroup ( n  = 58), were compared with an historical cohort (pre-DVD, n  = 114). Primary outcome was HbA1c at first diabetes-antenatal visit. Secondary outcomes included preconception folic acid consumption, planned pregnancy and HbA1c recorded in the 6 months preconception. Results: Mean first visit HbA1c was lower post-DVD vs. pre-DVD: 7.5% vs. 7.8% [58.4 vs. 61.8 mmol/mol]; p  = 0.12), although not statistically significant. 53% and 20% of women with type 1 and 2 diabetes, respectively, viewed the DVD. The viewed-DVD subgroup were significantly more likely to have lower first visit HbA1c: 6.9% vs. 7.8% [52.1 vs. 61.8 mmol/mol], P  < 0.001; planned pregnancy (88% vs. 59%, P  < 0.001); taken folic acid preconception (81% vs. 43%, P  = 0.001); and had HbA1c recorded preconception (88% vs. 53%, P  < 0.001) than the pre-DVD cohort. Conclusions: Implementation of a preconception counselling resource was associated with improved pregnancy planning indicators. Women with type 2 diabetes are difficult to reach. Greater awareness within primary care of the importance of preconception counselling among this population is needed.